2013
DOI: 10.2139/ssrn.2326195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Enterprise Risk Management Implementation on the Firm Value of European Companies

Abstract: We aim to investigate the impact of the adoption of an Enterprise Risk Management (ERM) system on the enterprise value and to discover which are the determinants of this choice. Several economic actors have decided to face the current economic and financial complexity shifting from a Traditional silo-based Risk Management approach (TRM) to a more comprehensive one, the so called Enterprise Risk Management (ERM). Some academics have tried to investigate the effects of the ERM implementation on firm value, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
8
26
1
8
Order By: Relevance
“…The results of this research led us to identify the level of risk culture as a factor which has a positive, strong and significant impact on financial performance within manufacturing SMEs in Cameroon and others factors have a negative but significant impact. These results are in conformity with Giorgio et al, (2013) [15]who found that the management of risks has a positive impact on the value of European companies. This result confirms also the assertion of Green and Jennings-Mares (2008) which stipulates that the most important element in risk management throughout firms is a cultivation of a consistent risk culture.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this research led us to identify the level of risk culture as a factor which has a positive, strong and significant impact on financial performance within manufacturing SMEs in Cameroon and others factors have a negative but significant impact. These results are in conformity with Giorgio et al, (2013) [15]who found that the management of risks has a positive impact on the value of European companies. This result confirms also the assertion of Green and Jennings-Mares (2008) which stipulates that the most important element in risk management throughout firms is a cultivation of a consistent risk culture.…”
Section: Discussionsupporting
confidence: 92%
“…The results show that an increase in the level of ERM implementation in companies positively contributes to the value of the companies. Giorgio and al., (2013) [15]as for him examines the impact of adoption risk management on the value of company and on the determinants of the choice of risk management. Based on a sample of 200 companies in the financial and non-financial sector; their results showed that risk management has a positive impact on the value of the European companies.…”
Section: 2mentioning
confidence: 99%
“…This study measured growth rate by using the percentage increase in the organization's revenue. This measure was also used by Beasley et al, (2005) and Waweru and Kisaka, (2013). Data on the growth rate was collected from the questionnaire.…”
Section: Control Variablesmentioning
confidence: 99%
“…The results of research on ERM effect on the fi nancial performance of companies are mixed. Researches done by Gordon, Loeb andTseng (2009) andBertinetti, Cavezzali andGardenal (2013) on fi nancial and non-fi nancial companies show positive effect of ERM implementation to the company's market value measured by Tobin's Q, so as the research of insurance companies by Hoyt and Liebenberg (2011). On the other side, research of Pagach and Warr (2010) done on fi nancial and non-fi nancial companies and of McShane, Nair and Rustambekov (2011) conducted on insurance companies found no evidence of ERM's effect on performance and market value.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The existence of a risk management department is an important element of developed ERM but it does not mean the department has the support of CEO and board to encourage the production and dissemination of risk information, nor that it has the resources, leadership, and support to mitigate the principal risks identifi ed (Mikes and Kaplan, 2014). The second way to identify ERM fi rms is to search for evidence of ERM (through databases; such as Lexis Nexis and Dow Jones) by entering key words, such as "Chief Risk Offi cer", "enterprise risk management" and "risk committee" (Bertinetti, Cavezzali and Gardenal, 2013;Hoyt and Liebenberg, 2011;Eckles, Hoyt and Miller, 2014). ERM binary variable (0 = no ERM; 1 = ERM).…”
Section: Review Of the Literaturementioning
confidence: 99%